Doses de fósforo na produção das mudas e sua influência na produção e qualidade de tomate - Martins, Bruno Novaes Menezes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Considering the lack of studies related to phosphorus application in the production of tomato seedlings and its effect after transplantation to the harvesting stage, the aim of this study was to evaluate the effects of doses of phosphorus supplied by fertigation to the sown seedlings in coconut fiber base substrate, production and quality of tomato fruits. The experiment was conducted from August 2013 to January 2014 in São Manuel Experimental Farm, located in São Manuel, SP. The experimental design was used in a randomized complete block design with four replications. We evaluate six treatments (P doses): 0; 15; 30; 45; 60 and 75 mg of P L-1, using monoammonium phosphate (MAP of 10.5% of P and 9% of N,) as source of P and N. On the day of transplanting, it was evaluated: leaf area (cm2); seedling height (cm), stem diameter, seedling (mm), fresh weight of shoot and root (g planta-1), dry matter of shoots and roots (g planta-1). It wasalso evaluated plant production (kg), productivity (t ha-1), number of fruits per plant, diameter and height of fruit (mm), average weight per fruit (g fruit-1) and early production. It was evaluated physical and chemical characteristics of fruits in four crops: pH, titratable acidity, Soluble solids, reducing sugars, ascorbic acid, maturation index (Ratio), chlorophyll a and b, lycopene and β-carotene. The results support the conclusion that tomato seedlings grown on substrates coconut fiber containing phosphorus, respond to the increase in phosphorus supply with an increase in leaf area, seedling height, fresh weight of the area part and roots. However, the increases in vegetative characteristics of tomato seedlings provided by increase in phosphorus level did not favor increased productivity and fruit mass. Regarding the fruit's physical and chemical characteristics, the best quality seedling tomato favored due to the increase in phosphorus levels did not affect ...

Diante da carência de estudos relacionados à aplicação de fósforo na produção de mudas de tomate e seu efeito após o transplante até a fase de colheita, objetivou-se com o presente trabalho avaliar os efeitos das doses de fósforo, fornecido via fertirrigação às mudas semeadas em substrato a base de fibra de coco, na produção e qualidade de frutos de tomate. O experimento foi conduzido no período de agosto de 2013 a janeiro de 2014 na Fazenda Experimental São Manuel, situada no município de São Manuel-SP. Foi utilizado o delineamento experimental em blocos casualizados, com quatro repetições. Foram avaliados seis tratamentos (doses de P): 0; 15; 30; 45; 60 e 75 mg de P L-1, utilizando-se fosfato monoamônio (MAP, 10,5 % de P e 9% de N,) como fonte de P e N. No dia do transplante das mudas foram realizadas avaliações da área foliar (cm2); altura da plântula (cm), diâmetro do caule da plântula (mm), massa da matéria fresca da parte aérea e das raízes (g planta-1), massa da matéria seca da parte aérea e das raízes (g planta-1). Também foram avaliadas a produção por planta (kg), produtividade (t ha-1), número, de frutos por planta, diâmetro e altura dos frutos (mm), massa média por fruto (g fruto-1) e produção precoce. Já para as características físico-químicas dos frutos avaliaram-se em quatro colheitas o pH, acidez titulável, sólidos solúveis, açúcares redutores, ácido ascórbico, índice de maturação (ratio), clorofila a e b, licopeno e β-caroteno. Os resultados encontrados permitem concluir que plântulas de tomate crescidas em substratos fibra de coco contendo fósforo, respondem ao aumento no fornecimento de fósforo com incremento em área foliar, altura de plântula, massa da matéria fresca da parte área e de raízes. Porém, os incrementos em características vegetativas das mudas de tomate proporcionados pelo aumento na dose de fósforo não ...
Phosphorus levels in the seedlings production and its inlfuence on yield and quality of tomatoes
Keywords: Tomate - Mudas; Minerais na nutrição de plantas; Plantas - Efeito do fosforo; Fertirrigação; Plants, Effect of phosphorus on